Aplp1 interacts with Lag3 to facilitate transmission of pathologic α-synuclein - Mao, Xiaobo; Gu, Hao; Kim, Donghoon; Kimura, Yasuyoshi; Wang, Ning; Xu, Enquan; Kumbhar, Ramhari; Ming, Xiaotian; Wang, Haibo; Chen, Chan; Zhang, Shengnan; Jia, Chunyu; et al. (Nature Communications, 2024)
Pathologic α-synuclein (α-syn) spreads from cell-to-cell, in part, through binding to the lymphocyte-activation gene 3 (Lag3). Here we report that amyloid β precursor-like protein 1 (Aplp1) interacts with Lag3 that facilitates the binding, internalization, transmission, and toxicity of pathologic α-syn. Deletion of both Aplp1 and Lag3 eliminates the loss of dopaminergic neurons and the accompanying behavioral deficits induced by α-syn preformed fibrils (PFF). Anti-Lag3 prevents the internalization of α-syn PFF by disrupting the interaction of Aplp1 and Lag3, and blocks the neurodegeneration induced by α-syn PFF in vivo. The identification of Aplp1 and the interplay with Lag3 for α-syn PFF induced pathology deepens our insight about molecular mechanisms of cell-to-cell transmission of pathologic α-syn and provides additional targets for therapeutic strategies aimed at preventing neurodegeneration in Parkinson's disease and related α-synucleinopathies.
Gesehen am 03.03.2025